Nitrogen-doped porous carbon with well-balanced charge conduction and electrocatalytic activity for dye-sensitized solar cells. (March 2018) - Xiao, Nan; Song, Junwei; Wang, Yuwei; Liu, Chang; Zhou, Ying; Liu, Zhiqiang; Li, Mingyu; Qiu, Jieshan
Abstract: Nitrogen-doped porous carbon with well-balanced charge conduction and electrocatalytic activity were synthesized from nitrogen-rich pitch by hard-template method. The sample carbonized at 900 °C possessing high nitrogen content (7.11 wt.%) and large specific surface area exhibits high electrocatalytic activity in dye-sensitized solar cells. A fast charge conduction involving facile ion transport and rapid electron transfer can be attributed to the open framework structure and soft carbon nature of pitch derived porous carbon, respectively. Owing to these merits, the nitrogen-doped porous carbon delivers higher power conversion efficiency (8.75%) than that of the commercial Pt electrode (7.55%).